2015
DOI: 10.1039/c5fd00037h
|View full text |Cite
|
Sign up to set email alerts
|

Crystal nucleation from solutions – transition states, rate determining steps and complexity

Abstract: This introductory paper offers a contemporary view of crystal nucleation. We begin with a molecular interpretation of the transition state and then revisit the use of classical nucleation theory as a means of obtaining molecular scale information from kinetic data. Traditional physical organic chemistry has always utilised the combination of kinetics and thermodynamics in order to gain insight over reaction pathways. Here we demonstrate for the cases of sucrose and p-aminobenzoic acid how solution chemistry, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 38 publications
5
45
0
Order By: Relevance
“…In fact, in the present work, the growth time t g is decreased in the presence of DOSS in 40 % DMA -% water over the entire supersaturation range examined. The same relation has been found previously 40 for paminobenzoic acid in different solvents, and it was concluded that desolvation of the carboxylic acid group and formation of carboxylic acid dimers is the rate limiting step for nucleation as well as for crystal growth. Studies showing molecular additives to increase the nucleation rate are rather scarce, but it has been found 41 that tailor-made additives can accelerate the growth of γglycine along the fast growing pole by disruption of the solvation, and that crystal growth of Lalanine 42 is accelerated in the presence of L-valine enhancing the rate of surface diffusion.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…In fact, in the present work, the growth time t g is decreased in the presence of DOSS in 40 % DMA -% water over the entire supersaturation range examined. The same relation has been found previously 40 for paminobenzoic acid in different solvents, and it was concluded that desolvation of the carboxylic acid group and formation of carboxylic acid dimers is the rate limiting step for nucleation as well as for crystal growth. Studies showing molecular additives to increase the nucleation rate are rather scarce, but it has been found 41 that tailor-made additives can accelerate the growth of γglycine along the fast growing pole by disruption of the solvation, and that crystal growth of Lalanine 42 is accelerated in the presence of L-valine enhancing the rate of surface diffusion.…”
supporting
confidence: 86%
“…Similarly, in 70 % DMA -30 % water at S I =1.75 in the absence of DOSS, the habit of the Form I crystals was plate-like, and did not change upon the addition of 1 mg/mL or 5 mg/mL DOSS(Figure 4.) SEM images of MEF crystals prepared in the absence or presence of DOSS in 40 % DMA -60 % water, at S II =4 40. (isolated at 8 min) and at S II =2.20 (isolated at 15 min).…”
mentioning
confidence: 99%
“…by the properties of the solvation environment, there is considerable interest, both fundamental and technological, in understanding how the processes of clustering, nucleation and subsequent growth of a molecular crystal are affected by the solution chemistry. 7,8 However, even advanced spectroscopic techniques such as synchrotron radiation x-ray scattering or atomic force microscopy cannot give a complete understanding of these processes. 9 The interpretation of experimental measurements and, most importantly, the ability to predict how a new crystal phase nucleates and then grows increasingly depends on the use of computer simulations.…”
Section: Introductionmentioning
confidence: 99%
“…This leaves the nucleation of molecules with slow nucleation kinetics as one of the key challenges for tubular crystallizers. APIs typically belong to this last category due to their high molecular complexity, which is still increasing for recently developed drugs as indicated by their increasing molecular weights [11]. Slow nucleation kinetics can cause difficulties in tubular crystallizers, as residence times are limited and the stochastic nature of crystallization can make the induction times in the small volume of tubular crystallizers excessively long.…”
Section: Introductionmentioning
confidence: 99%